2014
DOI: 10.1007/s10533-014-9952-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased inorganic nitrogen leaching from a mountain grassland ecosystem following grazing removal: a hangover of past intensive land-use?

Abstract: Morag A. 2014. Increased inorganic nitrogen leaching from a mountain grassland ecosystem following grazing removal: a hangover of past intensive land-use? Biogeochemistry,. 125-138. 10.1007/s10533-014-9952-7 Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…In upland acid grassland, studies have shown higher nitrate leaching in ungrazed compared with grazed areas McGovern et al, 2014), but varying the grazing intensity did not change N cycling or losses . In long-term grazing exclosures, McGovern et al (2014) observed fundamental shifts in ecosystem properties such as C/N ratios and fungal/bacterial ratios, suggesting that complete grazing removal had led to a transition from grasslands with high N turnover which were N-limited to heathlands with slower N turnover which were N-saturated.…”
Section: Impacts On N Removal and N Cyclingmentioning
confidence: 82%
See 1 more Smart Citation
“…In upland acid grassland, studies have shown higher nitrate leaching in ungrazed compared with grazed areas McGovern et al, 2014), but varying the grazing intensity did not change N cycling or losses . In long-term grazing exclosures, McGovern et al (2014) observed fundamental shifts in ecosystem properties such as C/N ratios and fungal/bacterial ratios, suggesting that complete grazing removal had led to a transition from grasslands with high N turnover which were N-limited to heathlands with slower N turnover which were N-saturated.…”
Section: Impacts On N Removal and N Cyclingmentioning
confidence: 82%
“…In upland acid grassland, studies have shown higher nitrate leaching in ungrazed compared with grazed areas McGovern et al, 2014), but varying the grazing intensity did not change N cycling or losses . In long-term grazing exclosures, McGovern et al (2014) observed fundamental shifts in ecosystem properties such as C/N ratios and fungal/bacterial ratios, suggesting that complete grazing removal had led to a transition from grasslands with high N turnover which were N-limited to heathlands with slower N turnover which were N-saturated. By contrast, in dune grassland N leaching was 50% lower in ungrazed than in grazed plots (Hall et al, 2011), despite higher mineralisation rates (Ford et al, Table 1 Nitrogen budget for grasslands under different management regimes, showing the main N loss pathways, and net annual N accumulation (all data as kg N ha −1 yr −1 , unless specified).…”
Section: Impacts On N Removal and N Cyclingmentioning
confidence: 82%
“…In winter at some sites there is evidence (not shown) of throughput from nitrogen deposition which cannot be utilised when other factors are limiting (see e.g. McGovern et al (2014)). As expected, DOC concentrations are notably high in drainage from the Migneint peat area in the south of the catchment, and lowest at high elevations where peat is largely absent.…”
Section: Water Qualitymentioning
confidence: 99%
“…Grazers may help thwart shrub growth and many studies have found that they can increase plant diversity through mechanisms such as creating heterogeneity in the environment, reducing plant competition, and spreading seeds (Collins, Knapp, Briggs, Blair, & Steinauer, ; Lwiwski, ; Milchunas et al., ; Milchunas, Sala, & Lauenroth, ; Pavlü, Hejcman, Pavlü, & Gaisler, ). However, the effect of grazing can differ widely in different ecosystems and environmental conditions, for example depending on soil moisture and fertility, grazing intensity and breed, and the local evolutionary history of grazing (Bakker, Ritchie, Olff, Milchunas, & Knops, ; Liu et al., ; McGovern et al., ; Milchunas et al., ; Socher et al., ). Coastal grasslands tend to have sandy and nutrient‐poor soil (Neill et al., ), which may be problematic because reviews suggest the effects of grazing on plant species richness are more likely to be negative in nutrient‐poor or dry grasslands than on more fertile soils (Cingolani, Noy‐Meir, & Díaz, ; Kohyani, Bossuyt, Bonte, & Hoffmann, ; Milchunas & Lauenroth, ; Proulx & Mazumder, ; Stewart & Pullin, ).…”
Section: Introductionmentioning
confidence: 99%